Isomorphic and diverse institutions among turkish foundation universities - Mizikaci, Fatma (My University, 2010)
This study explores isomorphic changes in the private higher education institutions in Turkey. Within and across the institutions, isomorphic changes are common while diverse patterns are subject to having semi-elite characteristics. Within the limits of the national centralized system, these universities have emerged as distinctive organizations and few have grown into leading institutions competing with public universities. They became initiators in running different academic programs, curricula and administrative structures. The largest group of foundation universities bears the demand absorbing role showing isomorphic characteristics. Three critical elements of isomorphic change, coercive, mimetic and normative, were observed in these institutions. With the exception of small number of distinctive organizations showing semi-elite characteristics, foundation universities remain small and akin.
Keywords: Distinctive; Elite; Institutional isomorphism; Semi- elite; Turkish foundation universities